Japan's quest for a permanent Security Council seat : a matter of pride or justice? - Drifte, Reinhard (Houndmills, Basingstoke, Hampshire, New York : Palgrave Macmilla, 2000)
Japan has consistently been pursuing the goal of a permanent UN Security Council seat for 30 years. This book investigates the motives for this ambition, and how it has been pursued domestically and internationally. It is therefore a study of the interior workings of the Japanese Foreign Ministry as well as of the country's underdeveloped multilateral diplomacy.
"In association with St. Antony's College, Oxford."
Includes bibliographical references (p. 246-260) and index.
Keywords: United Nations -- Security Council -- Membership; United Nations; Japan -- Foreign relations -- 1989--